Physiological responses and transcriptomic analysis of StCPD gene overexpression in potato under salt stresses - Zhou, Xiangyan; Ma, Yanming; Miao, Rong; Li, Caijuan; Liu, Ziliang; Zhang, Dan; Chen, Sijin; Luo, Jiaqi; Tang, Wenhui (Frontiers in Plant Science, 2024)
Introduction The potato (Solanum tuberosum L.), one of the most vital food crops worldwide, is sensitive to salinity. Brassinosteroids (BRs) are crucial in tolerance to various abiotic stresses. The constitutive photomorphogenesis and dwarf (CPD) gene encodes C-3 oxidase, which is a rate-limiting enzyme that controls the synthesis of BRs. Methods In this study, we used StCPD gene overexpression (T) and un-transgenic (NT) plants obtained from our former research to illustrate adaptive resistance to salt stress at levels of phenotype; cell ultrastructure, physiology, and biochemistry; hormone; and transcription. Results Results showed the accumulation of 2,4-epibrassionolide (EBL) in T potatoes. We found that under high salt situations, the changed Na+/K+ transporter gene expression was linked with the prevalent ionic responses in T plants, which led to lower concentrations of K+ and higher concentrations of Na+ in leaves. Furthermore, RNA-sequencing (RNA-seq) data elucidated that gene expressions in NT and T plants were significantly changed with 200-mM NaCl treatment for 24 h and 48 h, compared with the 0-h treatment. Functional enrichment analysis suggested that most of the differentially expressed genes (DEGs) were related to the regulation of BR-related gene expression, pigment metabolism process, light and action, and plant hormone signal transduction. Discussion These findings suggested that StCPD gene overexpression can alleviate the damage caused by salt stress and enhance the salt resistance of potato plantlets. Our study provides an essential reference for further research on BR regulation of plant molecular mechanisms in potatoes with stress tolerance.